Performances of 2 and 4 years-old culms of gigantochloa scortechinii (Buluh Semantan) in short term durability study - Muhammad Hafiz Hafzam Ahmad (2014)
This study investigates the performances of 2 and 4 years-old culms of Gigantochloa Scorfechinii (Buluh Semantan) in short term durability study. This study divided into two parts which are to identify the physical properties (moisture content and basic density) of G.scortechinii based on group age (2 and 4 year-old) and also to compare the durability properties of G. scortechinil between untreated and by using oil-curing process based on different group aged (2 and 4 year-old) by using grave-yard test for 4 months The results of the study showed that the oil-cured process greatly enhanced the durability of bamboo against biodegradation agents compare to the untreated. There is an overall decrease in moisture content of green bamboo samples and increase in basic density proportional to age after physical properties test which were the mean moisture content of bamboo sample of 2 years old is 36% and for 4 years old is 30.63°A.The mean basic density for 2 years old is 0.79 g/cm³ and for 4 years old is 1.1 g/cm³.The results for durability grave yard test shows significant increase of mean weight loss of bamboo samples according to months. For 2 years old, the mean weight loss of samples of 1st month is 8.11%,2nd month is 8.95%,3ʳᵈ month is 9.04% and month reached until 9.23%.For 4 years old, the mean weight loss of samples of 1ˢᵗ month is 7.37%,2ⁿᵈ month is 7.83%,3ʳᵈ month is 8.14% and finally 4ᵗʰ month is 9.32%.